Mass Shootings, Mental Illness, and Gun Control - Philpott-Jones, Sean (The Hastings Center report, 2018)
In the wake of the Stoneman Douglas School shooting, Republican and Democratic leaders—like the American electorate they represent—remain sharply divided in their responses to gun violence. They are united in their condemnation of these mass shootings, but they disagree about whether stricter or looser gun control laws are the answer. Those on the right side of the political aisle suggest that the issue is one of mental illness rather than gun control. Conversely, those who are more liberal or progressive in their political learnings are quick to condemn attempts to reframe the issue of mass shootings as a mental health problem. Both sides are wrong. Mass shootings are indeed partially a mental health problem, albeit one poorly addressed by our current laws and policies. But the solution to mass shootings also needs to consider strategies that may reduce gun violence in general.